Evaluation on the performance of cross-matrix absorber double-pass solar air heater (CMA-DPSAH) with and without thermal energy storage material - Sharol, Ahmad Fadzil; Abdul Razak, Amir; Abdul Majid, Zafri Azran; Azmi, Muhammad Amirul Azwan; Muhammad Tarminzi, Muhammad Amir Syahiran (Penerbit Akademia Baru, 2020)
The intermittent nature of solar energy source can reduce the performance of solar air heater (SAH) considerably. The utilization of thermal storage materials demonstrates an effective way in order to improve an overall performance of SAH. In the present study, the performance of cross-matrix absorber double-pass solar air heater (CMADPSAH) integrated with the phase change material (PCM) as thermal energy storage was conducted. The PCM material was inserted inside the rectangular aluminium tube used as the thermal absorber. The air mass flow rate of 0.004 kg/s was used during the entire experimental period. The experiment was conducted on several phase; Phase 1 (CMA-DPSAH with PCM) and Phase 2 (CMA-DPSAH without PCM) in order to compare and evaluate the effectiveness of the PCM utilization. Based on the result, CMA-DPSAH with PCM performed better than the CMA-DPSAH without PCM with maximum of heat gain and temperature output were 127 W and 53 oC, respectively. The instantaneous efficiency of CMA-DPSAH with PCM consistently higher than the CMA-DPSAH without PCM for about 17 – 19% with the maximum was 64 % during the low radiation flux. This feature offers a great potential of solar air heater application in the intermittent solar radiation condition, especially for drying of the agriculture products.